Study of the decay Bs0→Ds(*)Ds(*) - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (American Physical Society (APS), 2007)
We report a study of the decay Bs0→Ds(*)Ds(*) using a data sample corresponding to 1.3fb-1 of integrated luminosity collected by the D0 experiment in 2002-2006 during run II of the Fermilab Tevatron collider. One Ds(*) meson was partially reconstructed in the decay Ds→ μν, and the other Ds(*) meson was identified using the decay Ds→ π where no attempt was made to distinguish Ds and Ds* states. For the branching fraction Br(Bs0→Ds(*)Ds(*)) we obtain a 90% C.L. range [0.002,0.080] and central value 0.039-0.017+0.019(stat)-0.015+0.016(syst). This was subsequently used to make the most precise estimate of the width difference ΔΓsCP in the Bs0-B̄s0 system: ΔΓsCP/ Γs=0.079-0.035+0.038(stat)-0.030+0.031(syst). © 2007 The American Physical Society.